XRCC1 Is a Promising Predictive Biomarker and Facilitates Chemo-Resistance in Gallbladder Cancer - Wu, Zhengchun; Miao, Xiongying; Zhang, Yuanfang; Li, Daiqiang; Zou, Qiong; Yuan, Yuan; Liu, Rushi; Yang, Zhulin (Frontiers in Molecular Biosciences, 2020)
Gallbladder cancer is a relatively uncommon human malignant tumor with an extremely poor prognosis. Currently, no biomarkers can accurately diagnose gallbladder cancer and predict patients’ prognosis. XRCC1 is involved in tumorigenesis, progression, and chemo-resistance of several human cancers, but its role of XRCC1 in gallbladder cancer is never reported. In this study, we investigated the expression XRCC1 and its clinicopathological significance in gallbladder cancer and explore the biological role of XRCC1 in gallbladder cancer cells. We found that XRCC1 was significantly up-regulated in gallbladder cancer in protein and mRNA levels. Positive XRCC1 expression was correlated with aggressive clinicopathological features and was an independent poor prognostic factor of patients with gallbladder adenocarcinoma or squamous cell/adenosquamous carcinoma. The ROC curves suggested that XRCC1 expression has potential clinicopathological diagnostic value in gallbladder cancer. In vitro, XRCC1 was overexpression in CD133+GBC-SD cells compared to GBC-SD cells. In functional experiment, XRCC1 knockdown had a non-significantly impact on proliferation, migration, invasion, and apoptosis of CD133+GBC-SD cells. But, XRCC1 knockdown could significantly improve the sensitivity of CD133+GBC-SD cells to 5-Fluorouracil via promoting cell necrosis and apoptosis. Thus, this study indicated that XRCC1 may be a promising predictive biomarker of gallbladder cancer and a potential therapeutic target for gallbladder cancer.